Beyond nephronophthisis: Retinal dystrophy in the absence of kidney dysfunction in childhood expands the clinical spectrum of CEP83 deficiency. Issue 7 (3rd May 2021) - Veldman, Bram C. F.; Kuper, Willemijn F. E.; Lilien, Marc; Schuurs‐Hoeijmakers, Janneke H. M.; Marcelis, Carlo; Phan, Milan; Hettinga, Ymkje; Talsma, Herman E.; van Hasselt, Peter M.; Haijes, Hanneke A.
Abstract: The CEP83 protein is an essential part in the first steps of ciliogenesis, causing a ciliopathy if deficient. As a core component of the distal appendages of the centriole, CEP83 is located in almost all cell types and is involved in the primary cilium assembly. Previously reported CEP83 deficient patients all presented with nephronophthisis and kidney dysfunction. Despite retinal degeneration being a common feature in ciliopathies, only one patient also had retinitis. Here, we present two unrelated patients, who both presented with retinitis pigmentosa, without nephronophthisis or any form of kidney dysfunction. Both patients harbor bi‐allelic variants in CEP83 . This report expands the current clinical spectrum of CEP83 deficiency. For timely diagnosis of CEP83 deficiency, we advocate that CEP83 should be included in gene panels for inherited retinal diseases.